"I feel like God doesn't like me": Faith and Ambiguous Loss Among Transgender Youth. Issue 2 (19th January 2021) - Okrey Anderson, Sloan; McGuire, Jenifer K.
Abstract : Objective: The present study expands the use of ambiguous loss theory into the realm of religion and religious rejection for sexual‐ and gender‐minority people, an area that has previously been addressed primarily as an issue of minority stress. Background: Research has demonstrated that religion‐based, nonaffirming messaging from family and faith communities is correlated with decreased health and well‐being of sexual‐ and gender‐minority persons, who are, like most Americans, likely to have been raised in religious (predominately Christian) homes. Existing research has begun to explain why nonaffirming faith affiliation seems to negatively impact sexual gender minority people, but it does not explain the mechanisms of long‐term distress. Methods: This study is a qualitative thematic analysis of religion and family data from semistructured interviews with 63 transgender youth from the United States, Canada, and Ireland who reported being raised in religious Christian homes. Results: Analysis revealed that the narratives of participants who had been members of a psychological family of faith included all of the core elements of ambiguous loss, suggesting that individuals can experience ambiguous loss in relationship to a faith community and to God. Discussion: This study presents a new application of Boss's ambiguous loss theory and offers a framework for understanding why sexual‐ and gender‐minority people from Christian backgrounds might experience long‐term distress in relation to faith and spirituality whether they stay in their faith communities of origin or move on to something else. Implications: The experiences of transgender people examined through the framework of ambiguous loss and the concept of the psychological family of faith could be applied to research with people from any demographic in relation to loss of faith or faith community. This information may contribute to the study of family ruptures that occur as a result of family experiences of ideological or moral incompatibility (e.g., deconversion, political realignment, leaving a cult).